2012
DOI: 10.1111/j.1467-6281.2012.00382.x
|View full text |Cite
|
Sign up to set email alerts
|

The Failure of the Capital Asset Pricing Model (CAPM): An Update and Discussion

Abstract: Dempsey (2013) argues that, contrary to the generally held view, the capital asset pricing model (CAPM) has never merited an empirical justification. Additionally, he considers that if investors care about their exposure to the markets (requiring an equity risk premium) but are apparently indifferent to how that exposure is encapsulated in any stock (the measure of which is beta), then it is difficult to see how investors can be sensitive to the risk factors in the Fama and French (1996) threefactor model as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…These results are also corroborated by Fama and French (1996) and Jegadeesh and Titman (2001) in the US and other markets like the Asian ones (Rouwenhorst, 1998;Chui, Wei, & Titman, 2000) and emerging markets (Rouwenhorst, 1999). In the United States, Hammami (2013) shows that the momentum effect exists only for periods characterized by low market premium (good times), while Bornholt (2013) shows that the anomaly disappears when working on sectoral costs of equity capital.…”
Section: The Capm and Its Criticsmentioning
confidence: 55%
“…These results are also corroborated by Fama and French (1996) and Jegadeesh and Titman (2001) in the US and other markets like the Asian ones (Rouwenhorst, 1998;Chui, Wei, & Titman, 2000) and emerging markets (Rouwenhorst, 1999). In the United States, Hammami (2013) shows that the momentum effect exists only for periods characterized by low market premium (good times), while Bornholt (2013) shows that the anomaly disappears when working on sectoral costs of equity capital.…”
Section: The Capm and Its Criticsmentioning
confidence: 55%
“…The positive association, on the other hand, is suggested by the Keynesian approach since there exists positive relationship are present between economic activity and price level and therefore there must be a positive association between activity and the stock returns. Bornholt (2013) expanded on the popular CAPM and developed an equilibrium asset pricing model in which positive inflation rate and low earnings systems are connected with increase in overall stock return. The two studies by Dempsey (2013) and Bornholt (2013) demonstrated the inconclusiveness of different study outcomes and methodologies on the nexus between stock returns and economic fundamentals.…”
Section: Introductionmentioning
confidence: 99%
“…Tellingly, Bornholt () in his response extends their analysis to end‐2009 (confirming the general non‐applicability of the CAPM, but noting nonetheless that the beta anomaly has weakened in more recent times). Bornholt considers that as the continued existence of non‐compliance with the CAPM offers investing opportunities (invest in low beta assets and avoid high betas), the market must eventually learn to comply with the CAPM.…”
mentioning
confidence: 85%